Optimizing root architecture with nitrogen fertilization to improve nitrogen accumulation and yield in soybean - Xu, Yaxin; Zhang, Jianxin; Gao, Quantong; Wang, Cong (Frontiers in Plant Science, 2026)
IntroductionXinjiang is a high-yielding region for soybean in China, but issues such as low nitrogen use efficiency limit yield. Optimizing nitrogen fertilization strategies can effectively alleviate these problems.MethodsA two-year field experiment was conducted during the 2022 and 2023 growing seasons using a split-plot design. Two soybean cultivars, the low-yielding Xindadou 27 and the high-yielding Xinnongdou 2, were planted in the main plots. Four nitrogen application rates were applied in the subplots: 0, 120, 180, and 240 kg ha-1.ResultsThe application of 180 kg ha-1 nitrogen significantly increased root dry weight density, length density, and surface area density in the 0–60 cm soil layer, mainly through increases in the 0–20 cm soil layer. This treatment also enhanced the activities of key nitrogen metabolism enzymes (NR and GS/GOGAT) in roots, promoting nitrogen uptake and translocation to shoots, which increased both yield and shoot nitrogen accumulation. The higher accumulation rate and longer duration under the 180 kg N ha-1 application rate resulted in the highest root nitrogen accumulation. In contrast, a nitrogen application rate of 240 kg N ha-1 inhibited root growth, disrupted root nitrogen metabolism, and reduced root nitrogen accumulation. Structural equation modeling confirmed that root growth parameters have a positive influence on root nitrogen accumulation.DiscussionThis study demonstrates that application of 180 kg N ha-1 at the beginning pod stage promotes root development, improves NUE and yield for spring soybean in Xinjiang. It is recommended as a sustainable high-yield practice for the region.